Governance of Multi-sectoral Interventions to Promote Healthy Living in Latin America and the Caribbean - Bonilla-Chacín, María E. (World Bank, Washington, DC, 2014)
The Latin America and Caribbean (LAC) region has been experiencing a rapid demographic and epidemiological transition which has important health and economic consequences. Not only is the population aging rapidly, but it is also experiencing major changes in lifestyle. This has altered the disease and mortality profile, reflected in the increasing weight of Non-Communicable Diseases (NCDs), such as heart disease, stroke, cancer and diabetes. These conditions also represent an increasing economic and development threat to households, health systems, and economies. The study also ranked tobacco use among the first five risk factors in LAC and alcohol abuse as the main risk factor in all sub-regions, with the exception of the Caribbean and southern LAC, where alcohol was ranked among the first five. However, voluntary actions are often ineffective and policymakers have replaced them with regulations. For example, in Europe, Canada, and the US, early voluntary nutrition labeling actions failed to meet government standards and expectations which led governments to use mandatory guidelines. In New York City, authorities encouraged restaurants to voluntarily provide easily-seen nutrition information to customers, but, as this did not occur, the City passed a regulation. In general, policymakers and health advocates often gauge and mobilize public opinion to support these health promotion policies and ensure their design and implementation.